Analisis Implementasi Media Video Pembelajaran Tematik di Kota Semarang - Retno Nilawati; Diana Endah Handayani; Mei Fita Asri Untari (STKIP Andi Matappa Pangkep, 2022)
The Covid-19 pandemic is now having an impact on the world of education which causes changes in teaching and learning activities to be online. The development of science and technology during the pandemic has been felt such as the creation of new learning methods and presenting a variety of media or learning resources, one of which is using learning videos. The purpose of this study is to determine the implementation of thematic learning video media, especially for grade 3 students. This type of research uses a qualitative research type with a descriptive approach. Methods of data collection using interview techniques, observation, filling out questionnaires and documentation. The results of the analysis show that the principal provides periodic evaluations with the teacher on the implementation of learning using thematic learning video media. Learning using thematic learning video media using the Youtube, Google Classroom, and Whatsapp group platforms. The requirements for good thematic learning video media during the pandemic are the content of the video according to the material being taught, in accordance with basic competencies and content standards, interesting, easy to understand, using good language, achieving learning objectives, not containing pornographic elements and the spelling used is appropriate. with EYD.